Charakter prawny umowy deweloperskiej w prawie hiszpańskim: [Legal nature of contract for the sale of real property in Spain] (Studia Prawnicze / The Legal Studies, 2010)
Hiszpański rynek nieruchomości wskutek światowego kryzysu gospodarczego odniósł najbardziej dotkliwe straty ze wszystkich krajów europejskich. Światowy kryzys gospodarczy rozpoczął się na amerykańskim rynku nieruchomości w sierpniu 2007 r., następnie przeniósł się na rynki europejskie. Spośród wszystkich krajów Europy właśnie Hiszpania najbardziej odczuła to gwałtowne załamanie koniunktury. Giełda hiszpańska (Ibex) odnotowała najwyższe spadki w Europie.Wielu ekspertów, zarówno w Stanach Zjednoczonych, jak i w innych krajach, w tym europejskich, ostrzegało już od dłuższego czasu o niebezpieczeństwach związanych z hipotekami „subprime” tzw. wysokiego ryzyka, udzielanymi klientom, których wypłacalność/zdolność kredytowa była bardzo wątpliwa, a stopy oprocentowania ich kredytów były wyższe od przeciętnych, co z kolei pociągało za sobą duże prawdopodobieństwo, iż już znajdując się w niestabilnej sytuacji finansowej, nie będą oni w stanie spłacać również i tych kredytów. The present work is supposed to describe the legal nature of contract for the sale of property in Spain. The article refers mainly to the contracts for the sale of new apartments which are still under construction, or have only just been planned without any building works having been started yet, so – called ‘developing contracts’ in Polish. Contracts for the sale of real properties are of utmost importance in the economy of the country in many different regards. First, because of the legal complexities involved in this process, very often connected with signing the mortgage agreement at the same time. Second, from the economic point of view, since in most cases it is the most important financial decision in the life of the purchaser of the apartment. Third, just looking at this process from the human side, because apartment is the place where the buyer and his family spend most of their time. Taking all that into consideration, the Spanish law maker decided to regulate this matter in a very thorough way. There are many legal acts involved in regulating this process, like Spanish civil code, Act 1/2007 on protection of consumers, Act 515/1989 on the information duties in the contract for the sale of real property, Act 38/1999 on construction, and Act 57/1968 on advance payments. All of them create legal complexities of the contract for the sale of real properties, which as has been emphasized in the article is, as a rule, a contract for the sale of future thing in Spanish law. Generally, Spanish regulation concerning this type of contracts should be evaluated in a very positive way, since the consumer stands there in the first position and is protected against the abuses and malpractices coming from the developer not only by a number of regulations created by the lawmaker, but also by a rich body of rulings passed by judges in this area of law.